Rancangan Ulang Tata Letak IKM Buska Indah Menggunakan Metode SLP dan Grafik - Alparadi, Bima; Fitra, Fitra; Syahputra, T.M. Habil; Pangihutan, Agus (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Buska Indah Small and Medium Enterprises (SMEs) produce household furniture such as chairs, doors, and windows. The results show that the production facility layout at Buska Indah SME is still inefficient. This is indicated by disorganized workflow, long material handling distances, and accumulation of goods in several locations that can disrupt production. These conditions lead to inefficient time usage and increased operator workload. In this study, the layout was redesigned with the aim of identifying, assessing, and controlling ergonomic factors at the workplace. The Systematic Layout Planning (SLP) method and the graph method were used to solve the problem. An efficient layout can be achieved by utilizing both approaches to reduce material handling distances and labor costs. Analysis results indicate that the proposed layout using the SLP method has the smallest travel distance, 118.8 m², compared to the graph method. producing a displacement distance of 177.1 m². As a result, the SLP method was chosen as the best alternative. The proposed layout for IKM Buska Indah requires a production area of 446.95 square meters. Therefore, IKM Buska Indah must consider and readjust the production area to make work activities more efficient and ergonomic. Keywords: Graphical Method, Layout, Systematic Layout Planning